UNIVERSITY, EDUCATION AND RESEARCH: WHAT IS IN DEBATE? (Imagens da Educação, 2021)
We present the thematic issue that gathers 10 articles around the necessary struggle for the defense of the University, Training and Research as a critical-political-social set of freedom; professional practice; of collaboration, questioning and transformation of the current political situation.